Estimating photosynthetic activity in microbial mats in an ice‐covered Antarctic lake using automated oxygen microelectrode profiling and variable chlorophyll fluorescence. (7th April 2014) - Hawes, Ian; Giles, Hilke; Doran, Peter T.
Abstract : An automated oxygen microprofiler measured a positive flux of oxygen from microbial mats in ice‐covered Lake Hoare, Antarctica, from noon, at a photon flux of 20 µmol m −2 s −1, through to midnight (< 2 µmol photons m −2 s −1 ). Daily average oxygen flux was 200 µmol m −2 h −1 ; and, whereas it was maximal at noon, when a 10 mm broad concentration peak was observed 5 mm below the mat surface, flux correlated only weakly with irradiance. In contrast, relative electron transfer rate, estimated from variable chlorophyll fluorescence, suggested a linear relationship between photosystem activity and irradiance. This contradiction arose because of the conjunction of photosynthetic production of oxygen deep into these transparent, gelatinous mats (diel oxygen change was observed to 17 mm depth) and oxygen diffusion rates too slow to allow equilibration of oxygen concentration profiles with instantaneous production and consumption of oxygen. To confirm this, we developed a mathematical simulation of oxygen dynamics that included diffusion, photosynthesis, and respiration. The simulation further indicated that (1) net oxygen evolution is light limited is and confined to the upper few millimeters of the mat, (2) below 5–7 mm, respiration balanced photosynthesis, (3) below 17 mm, respiration and photosynthesis approached zero, even though organic carbon and dissolved oxygen were present, and (4) photosynthesis deep into the mat was dependent on high light transmission through the gelatinous matrix. These conclusions are consistent with current understanding of mat growth dynamics and point to approaches for long‐term analysis of microbial mat productivity.